(untitled) (Law Research Review Quarterly, 2026)
Economic modernization and globalization have significantly transformed the structure and dynamics of national economies, including Indonesia’s economic system. These developments pose substantial challenges to the existing framework of economic law, which must adapt to rapid technological advancements, cross-border economic activities, and increasing global competition. This study aims to analyze the influence of economic modernization and globalization on Indonesian economic law and to examine the necessity of reorienting economic law reform to address these challenges effectively. This research employs a normative legal research method with a statutory and conceptual approach, examining relevant laws, regulations, and legal doctrines related to economic law in Indonesia. The analysis focuses on identifying structural limitations within current legal frameworks and evaluating their responsiveness to global economic changes. The findings indicate that Indonesian economic law reform has not fully accommodated the complexities of economic modernization and globalization, particularly in ensuring regulatory adaptability, legal certainty, and balanced protection between national economic interests and global market demands. Therefore, a reorientation of economic law reform is essential to create a more adaptive, inclusive, and competitive legal framework. This study contributes to the development of economic law by offering a conceptual framework for reorienting Indonesian economic law reform in line with contemporary economic realities and global economic integration.